Nurturing Excellence: Association of Surgeons in Training Annual Conference 2018 Edinburgh. (July 2019) - Mohan, H.M.; Deekonda, P.; Humm, G.; ,
Abstract: The Association of Surgeons in Training (ASiT)'s motto is the pursuit of excellence in surgical training. The Association provides support to surgical trainees throughout the United Kingdom and Republic of Ireland. Originally founded in 1976, ASiT is independent of the National Health Service (NHS), Surgical Royal Colleges, and specialty associations. The 2018 Annual Conference in Edinburgh hosted over 800 delegates for a packed educational weekend. The conference theme was #nurturingexcellence and focused on helping trainees achieve their potential and improve surgical care. The importance of support for diversity in surgery was emphasised. An inclusive approach was fostered with a baby feeding room and a clear message that babies were welcome at the conference. Debates on the role of simulation in surgical training, sessions on reflective practice and the improving surgical training programme and a question and answer session with the presidents of the Royal colleges of surgeons made for lively and at times heated discussions. The weekend started with pre-conference courses covering a diverse range of topics including core laparoscopic, vascular, orthopaedics, neurosurgical skills, leadership, NOTSS and global surgery. Over 1000 abstract submissions were received and there were over 30 prize winning submissions. ASiT continues to grow and we look forward to an even larger and more successful international conference next year in Belfast 22nd-24th March, with an exciting parallel Hackathon to foster cross specialty cooperation to solve surgical problems. Highlights: Nurturing Excellence was the theme of ASiTs 2018 Conference in Edinburgh. Supporting trainees to achieve their potential is essential. ASiTs next conference will be 22–24th March 2019 in Belfast with a theme of Innovation in Surgical Practice.